The Malay Islamic Monarchy (MIB) and the Future of Islamic Higher Education in Brunei Darussalam - Rahman, Muhammad Amsyar; Jumat, Irfan Hakim; Sulaiman, Amira Sofea (Jurnal Penelitian Pendidikan Islam, 2026)
This article examines the Malay Islamic Monarchy, commonly known as MIB, as a foundational framework for understanding the future of Islamic higher education in Brunei Darussalam. It argues that MIB is not merely a symbolic national ideology, but a moral, cultural, epistemological, and governance framework that shapes educational policy, curriculum orientation, teacher formation, institutional identity, and graduate expectations. Using a qualitative library-based approach, the article analyzes scholarly works and policy-related studies on MIB, Islamic education, Brunei’s education system, bilingual policy, digital transformation, teacher education, and Islamic finance. The discussion shows that Islamic higher education in Brunei faces a complex task. It must preserve Islamic values, Malay cultural identity, and monarchical legitimacy while responding to globalization, English-medium academic culture, digital learning, economic diversification, and international higher education standards. The article proposes an adaptive MIB-based model of Islamic higher education built on ideological continuity, integration of naqli and aqli knowledge, reflective pedagogy, bilingual competence, ethical digital engagement, and institutional accountability. The study contributes to the discourse on Islamic higher education by showing how a national Islamic philosophy can function not only as a mechanism of identity preservation, but also as a dynamic framework for educational renewal and global relevance.